2013
DOI: 10.1111/jcmm.12172
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the immune system as a critical step for bone formation from allogeneic osteoprogenitors implanted in rats

Abstract: The surface marker profile of mesenchymal stromal cells (MSCs) suggests that they can escape detection by the immune system of an allogeneic host. This could be an optimal strategy for bone regeneration applications, where off-the-shelf cells could be implanted to heal bone defects. However, it is unknown how pre-differentiation of MSCs to an osteogenic lineage, a means of improving bone formation, affects their immunogenicity. Using immunohistological techniques in a rat ectopic implantation model, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…However, at the time of explantation, we found a negative correlation between the presence of lymphoid cell clusters and the amount of bone tissue formation caused by BMP-2. In agreement with others (Chatterjea et al, 2014), we show that these cell infiltrations are likely a mixed population of B and T cells. Interestingly, LTA-loaded constructs presented the lowest number of lymphoid cells, while the opposite association was seen for LPS-loaded constructs.…”
Section: Croes Et Alsupporting
confidence: 77%
See 1 more Smart Citation
“…However, at the time of explantation, we found a negative correlation between the presence of lymphoid cell clusters and the amount of bone tissue formation caused by BMP-2. In agreement with others (Chatterjea et al, 2014), we show that these cell infiltrations are likely a mixed population of B and T cells. Interestingly, LTA-loaded constructs presented the lowest number of lymphoid cells, while the opposite association was seen for LPS-loaded constructs.…”
Section: Croes Et Alsupporting
confidence: 77%
“…Alternatively, their activation could also occur secondarily to the innate immune response (MacLeod et al, 2007;Zanin-Zhorov et al, 2007). The local presence of adaptive immune cells can be both stimulatory (Nam et al, 2012;Ono et al, 2016) or inhibitory (Chatterjea et al, 2014;Liu et al, 2011;Reinke et al, 2013) for bone regeneration, and is likely dependent on the contribution of specific T cell subsets.…”
Section: Croes Et Almentioning
confidence: 99%
“…Similarly, Liu and colleagues [ 7 ] and Arinzeh and colleagues [ 32 ] implanted ex vivo osteogenically differentiated cells in vivo in a leporine and canine model, respectively, and found that these cells incorporated into the host tissue, functioned as osteoblasts and resided in situ for at least 28 days without overt signs of rejection such as hypercellularity. In contrast to these data, however, it has been reported by others that implanted allogeneic MSCs require immunosuppressive treatment to survive and differentiate in vivo, and are rapidly cleared by infiltrating immune cells in the absence of such immunosuppression [ 34 , 35 ]. Additionally, expression of immunogenic molecules such as Swine leukocyte antigen-I (SLA-I) on differentiating allogeneic porcine MSCs was shown to reduce the in vivo efficacy of the treatment when compared to allogeneic MSCs that had SLA-I knocked down [ 36 ].…”
Section: Allogeneic Mesenchymal Stem Cells In Bone Regenerationmentioning
confidence: 98%
“…However, recently other studies have shown MHC II expression presents following stimulation with interferon gamma (41), after chondrogenic differentiation (42) (43) (44) or osteogenic differentiation (45). Others have found that immunosuppressive therapy is needed for differentiated MSC to survive and evade infiltrating immune cells (46, 47). This has raised concern for the longevity of allogeneic cells in the donor recipient (48) particularly for therapies where the differentiated cell type is important such as cartilage replacement in OA.…”
Section: Mode Of Action Of Msc Supplementationmentioning
confidence: 99%